Applying a set of termination of resuscitation criteria to paediatric out-of-hospital cardiac arrest. (December 2021) - Harris, Matthew I.; Crowe, Remle P.; Anders, Jennifer; D'Acunto, Salvatore; Adelgais, Kathleen M.; Fishe, Jennifer
Abstract: Objective: Prehospital Termination of Resuscitation (TOR) protocols for adults can reduce the number of futile transports of patients in cardiac arrest, yet similar protocols are not widely available for paediatric out-of-hospital cardiac arrest (POHCA). The objective of this study was to apply a set of criteria for paediatric TOR (pTOR) from the Maryland Institute for Emergency Medical Services Systems (MIEMSS) to a large national cohort and determine its association with return of spontaneous circulation (ROSC) after POHCA. Methods: We identified patients ages 0–17 treated by Emergency Medical Services (EMS) with cardiac arrest in 2019 from the ESO dataset and and applied the applicable pTOR certeria for medical or traumatic arrests. We calculated predictive test characteristics for the outcome of prehospital ROSC, stratified by medical and traumatic cause of arrest. Results: We analyzed records for 1595 POHCA patients. Eighty-eight percent ( n = 1395) were classified as medical. ROSC rates were 23% among medical POHCA and 27% among traumatic POHCA. The medical criteria correctly classified >99% (322/323) of patients who achieved ROSC as ineligible for TOR. The trauma criteria correctly classified 93% (50/54) of patients with ROSC as ineligible for TOR. Of the five misclassified patients, three were involved in drowning incidents. Conclusions: The Maryland pTOR criteria identified eligible patients who did not achieve prehospital ROSC, while reliably excluding those who did achieve prehospital ROSC. As most misclassified patients were victims of drowning, we recommend considering the exclusion of drowning patients from future pTOR guidelines. Further studies are needed to evaluate the long-term survival and neurologic outcome of patients misclassified by pTOR criteria.